Epidemiological Profile of Femur Fracture Victims in the Last Five Years at a Referral Hospital in Ananindeua, Pará, Brazil - , Ana Clara De Melo Ferreira; , Lucas Pompeu Francez; , Poliana Viera Alves de Oliveira; , Werllison Mateus Silva Lobato; , Pedro Paulo da Fonseca Pinheiro; , Mayara Annanda Oliveira Neves Kimura; , Bruna Rafaela da Silva Sousa; , Yasmin Martins de Sousa (Archives of Current Research International, 2025)
Aims: This study aimed to describe the epidemiological profile of patients with femoral fractures treated at a referral hospital in Ananindeua, Pará, Brazil, between 2019 and 2023. Study Design: A descriptive, retrospective, and quantitative study. Place and Duration of Study: The study was conducted using data from a referral hospital in Ananindeua, located in the Metropolitan Region of Belém, Pará, covering the period from January 2019 to December 2023. Methodology: Secondary data were obtained from the Department of Informatics of the Unified Health System (DATASUS), through the TABNET platform. Variables analyzed included year of hospitalization, sex, age group, length of hospital stay, and mortality rate. Data were organized in spreadsheets and analyzed descriptively using absolute and relative frequencies. Results: The analysis revealed a higher prevalence of femoral fractures among elderly individuals, especially females. Most cases were concentrated in older age groups, with a considerable length of hospital stay observed among patients. A variation in the number of hospitalizations was noted throughout the study period, along with the presence of hospital mortality associated with the condition. Conclusion: The study highlights the vulnerability of the elderly population, particularly women, to femoral fractures. The findings reinforce the importance of preventive public health measures, early intervention strategies, and improved care for the aging population. The use of DATASUS proved to be an effective tool for epidemiological surveillance and healthcare planning.